2020
DOI: 10.1186/s12917-020-2230-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira infection and shedding in dogs in Thailand

Abstract: Background: Leptospirosis is a widespread zoonosis and has been recognized as a re-emerging infectious disease in humans and dogs, but prevalence of Leptospira shedding in dogs in Thailand is unknown. The aim of this study was to determine urinary shedding of Leptospira in dogs in Thailand, to evaluate antibody prevalence by microscopic agglutination test (MAT) and enzyme-linked immunosorbent assay (ELISA), and to assess risk factors for Leptospira infection. In Northern, Northeastern, and Central Thailand, 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 59 publications
6
31
0
Order By: Relevance
“…Compared to the present findings, the lower seroprevalence of leptospirosis was reported in Malaysia (3.1%), Thailand (4.4%), Brazil (7.1%), and Ethiopia. 7,28,41,42 On the contrary, the higher seroprevalence of Leptospira infection was reported by Aslantaş et al, 43 Delaude et al 44 and Pratt et al 45 In this study, the seroprevalence of the Brucella infection was comparable to the findings of Mosalanezhad et al, 47 who reported 4.9% from companion dogs in Ahvaz, Iran. The current finding is also consistent with the 7.5% seroprevalences of B. canis in shelter dogs in Turkey, 48 4.9% in Mississippi, 49 and 7.9% in Japan.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Compared to the present findings, the lower seroprevalence of leptospirosis was reported in Malaysia (3.1%), Thailand (4.4%), Brazil (7.1%), and Ethiopia. 7,28,41,42 On the contrary, the higher seroprevalence of Leptospira infection was reported by Aslantaş et al, 43 Delaude et al 44 and Pratt et al 45 In this study, the seroprevalence of the Brucella infection was comparable to the findings of Mosalanezhad et al, 47 who reported 4.9% from companion dogs in Ahvaz, Iran. The current finding is also consistent with the 7.5% seroprevalences of B. canis in shelter dogs in Turkey, 48 4.9% in Mississippi, 49 and 7.9% in Japan.…”
Section: Discussionsupporting
confidence: 74%
“…In Africa, Ethiopia ranks second only to Nigeria in the health burden of zoonotic diseases and stands in the first place as a hot spot of leptospirosis in the world. 52 The high humidity and rainfall in the studied towns coupled with the fact that infected dogs remain chronic carriers and shedders of Leptospira through their urine, 42 it is likely that the environment of the towns is contaminated, posing a risk of infection to other animals and humans. The present study showed the status of Brucella and Leptospira infections and their associated factors in dogs in the study area.…”
mentioning
confidence: 99%
“…It is of course possible that no positive cultures were detected due to storage and transport, but this is unlikely because at the same time urine samples from dogs were processed and cultured using the same methods. Of the dog samples, one was positive, which is a proof that the method of storage, transport, processing and culturing of cat and dog urine samples were adequate (Altheimer et al., ).…”
Section: Discussionmentioning
confidence: 92%
“…in their kidneys, shedding them into the environment via their urine ( 3 , 4 ). In Bangkok, Thailand, and metropolitan areas, the seroprevalence in stray dogs was observed to be 12.1 to 83.5%, and Leptospira interrogans serovar Bataviae was predominant ( 5 , 6 ). In this study, we present the draft genome sequence of an L. interrogans strain that was isolated from the urine of an asymptomatic dog in Pathum Thani, Thailand, in 2017.…”
Section: Announcementmentioning
confidence: 99%
“… Leptospira interrogans serovar Bataviae strain D64 was isolated from dog urine and was identified by urine culture, real-time PCR, and phylogenetic analysis, as described previously ( 5 ). Strain D64 was cultured at 28°C for 14 to 28 days in Leptospira medium base Ellinghausen-McCullough-Johnson-Harris (EMJH) (Thermo Fisher Scientific, USA) ( 7 ) supplemented with Leptospira enrichment EMJH (Thermo Fisher Scientific) and 3% rabbit serum (Thermo Fisher Scientific) under aerobic conditions and was observed by dark-field microscopy.…”
Section: Announcementmentioning
confidence: 99%